UTILIZING A WEBSITE TO INCREASE EDUCATION QUALITY AWARENESS IN WEST KALIMANTAN RURAL VILLAGES - Ernawaty, Ernawaty; Chandra, Yacob Utama (Social Economics and Ecology International Journal, 2017)
Education already become a basic human right since they were born. But geographical condition differentiates the level of education quality they get. Especially in most development countries with low implementation of ICT (Information, Communication, and Technology). In this digital era, it is hard to achieve an effective and efficient learning environment in rural areas. Infrastructures and teaching tools in those areas are very humble. Few books can be read. With limited educational background, social-economy issues will always keep remain. Love Borneo is an organic community that want to make a change for children in rural villages in West Kalimantan. They build a facility called Rumah Baca that provide good quality books suitable for children. They collect donated books and some money to buy books and educational games for children. Since 2015, they already build 10 Rumah Baca. But there are still so many villages that need this kind of facility. To build awareness about education for children in rural villages, this article discusses the development of a dedicated website called www.loveborneo.org that provides up to date information about this community and their activities. People around the world can access this website and can officially support this community. www.loveborneo.org is only one example of ICT implementation to help rural citizens.